The Way It Was. Issue 1 (2nd January 2016) - Teitz, Michael B.
Abstract: Reflecting on 50 years as a planning educator, Teitz describes planning education in one institution, the University of California, Berkeley, especially in the 1960s and 1970s, carrying through to the reorganization of the Association of Collegiate Schools of Planning (ACSP) in the 1980s. How theory and practice engaged him during that time and later is discussed through the lens of his involvement in research, teaching, and planning consultancy and the formative phases of two research institutes.